Profil Kemampuan Berpikir Kritis Siswa Kelas VIII SMP Pada Mata Pelajaran IPA - Ardia Tita Kartika; Lydea Eftiwin; Mahdiya Fitri Lubis; Ahmad Walid (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2020)
This research was conducted with the aim to determine the level of understanding of students in junior high school about science subjects. This research uses descriptive and qualitative methods as its consideration. In this study the sample consisted of 30 students in class VIII G and 28 students in class VIII H. Data collection techniques with Pre-test and Post-test about students' thinking abilities on junior high school material. The research instrument consisted of 15 Pre-test items and 15 Post-test questions that had been adjusted using rubrics. This study presents the results of research on eighth grade students. The results of the study showed students who used the problem-solving method to all participants who used the lecture method. The level of critical thinking skills in class of students is normally distributed, so that it can be completed increased.